Drivers of long-term variability in CO2 net ecosystem exchange in a temperate peatland - C. Helfter; C. Campbell; K. J. Dinsmore; J. Drewer; M. Coyle; M. Anderson; U. Skiba; E. Nemitz; M. F. Billett; M. A. Sutton (Biogeosciences, 2015)
Land–atmosphere exchange of carbon dioxide (CO2) in peatlands exhibits marked seasonal and inter-annual variability, which subsequently affects the carbon (C) sink strength of catchments across multiple temporal scales. Long-term studies are needed to fully capture the natural variability and therefore identify the key hydrometeorological drivers in the net ecosystem exchange (NEE) of CO2. Since 2002, NEE has been measured continuously by eddy-covariance at Auchencorth Moss, a temperate lowland peatland in central Scotland. Hence this is one of the longest peatland NEE studies to date. For 11 years, the site was a consistent, yet variable, atmospheric CO2 sink ranging from −5.2 to −135.9 g CO2-C m−2 yr−1 (mean of −64.1 ± 33.6 g CO2-C m−2 yr−1). Inter-annual variability in NEE was positively correlated to the length of the growing season. Mean winter air temperature explained 87% of the inter-annual variability in the sink strength of the following summer, indicating an effect of winter climate on local phenology. Ecosystem respiration (Reco) was enhanced by drought, which also depressed gross primary productivity (GPP). The CO2 uptake rate during the growing season was comparable to three other sites with long-term NEE records; however, the emission rate during the dormant season was significantly higher. To summarise, the NEE of the peatland studied is modulated by two dominant factors: - phenology of the plant community, which is driven by winter air temperature and impacts photosynthetic potential and net CO2 uptake during the growing season (colder winters are linked to lower summer NEE), - water table level, which enhanced soil respiration and decreased GPP during dry spells. Although summer dry spells were sporadic during the study period, the positive effects of the current climatic trend towards milder winters on the site's CO2 sink strength could be offset by changes in precipitation patterns especially during the growing season.